Unsusual manifestation of terra firme-forme dermatosis - upper eyelid and orbital rim - Uwe Wollina (Our Dermatology Online, 2018)
Terra firme-forme dermatosis is a benign exogenous dermatosis found in all age-groups. The typical localizations include neck, face, trunk and ankles. Here we report on an 88-year-old male with a medical history of stroke and paraplegia of the legs who presented with asymptomatic, hyperkeratotic and slightly hyperpigmented lesions on his upper lids. Wiping of skin with alcohol pads completely removed the lesions confirming the diagnosis of terra firme-forme dermatosis of upper eyelids. Although affection of lower eyelids has reported before, the localization on upper eyelids only is very unusual.